Pengaruh Analisis Pengelolaan Keuangan pada UMKM (Studi Kasus Angkringan di Jalan Teuku Umar Kedaton Bandar Lampung) - Nanda; Dea; Nita; Defrizal (CV. Creative Tugu Pena, 2024)
The aim of this research was to analyze the efficiency of financial management in micro, small and medium businesses carried out by micro, small and medium angkringan businesses on Jalan Teuku Umar Kedaton Bandar Lampung. The research was carried out using descriptive qualitative methods with a case study approach. Data collection techniques refer to the methods used to collect information or data required in a research or project. The data analysis technique used for this research is qualitative descriptive analysis, with the following analysis stages: inductive and descriptive analysis. The results of the research are that it is known that micro, small and medium enterprises on Jalan Teuku Umar Kedaton Bandar Lampung feel that they do not need a good planning, recording, reporting and management process in accordance with SAK for micro, small and medium enterprises even though they are aware that deficiencies in their financial management practices cause profit results. This is because the goal that micro, small and medium business actors on Jalan Teuku Umar Kedaton Bandar Lampung have in running their business is to fulfill their daily needs so that without these four processes the business goal can be achieved. Business expansion is something they have never thought about, therefore training is needed to provide micro, small and medium business entrepreneurs with a more personal understanding regarding good financial management. The process of borrowing capital from banks carried out by informants does not require business financial reports because the files used to obtain loan funds are from personal assets as collateral (land/house certificates). Capital loans are made when micro, small and medium enterprises want to open a business first, not to expand, because not all angkringan businesses have been passed down from generation to generation. This causes micro, small and medium enterprises to increasingly lack the motivation to make careful planning, careful record keeping, financial reports and overall good control.